Genetic Variability, Correlation And Path Analysis Of Fruit Yield In Spine Gourd (Momordica Dioica Roxb.) (Applied Biological Research, 2020)
The present study was conducted on 31 genotypes of spine gourd (Momordica  dioica Roxb.) to estimate genetic variability, correlation and path coefficient  analysis. The high estimates of PCV for the number of stem plant-1(21.47) and  moderate GCV and PCV observed for most of the traits which indicated the  presence of adequate genetic variation among the genotypes. High heritability  estimates coupled with high genetic advance for the number of fruits plant-1 and fruit yield confirmed that these traits are under the control of additive  gene action. Fruit yield showed significant positive association with days to  first flowering, number of stems plant-1, fruit weight and number of fruits  plant-1. The higher association of number of fruits plant-1, number of stem  plant-1, days to first flowering, fruit weight, fruit diameter and ovary diameter  may be attributed to their direct effect on fruit yield. The study showed that  the selection of traits with high positive significant association and high  positive direct effect on fruit yield can help in improving yield. The similarity  coefficient ranged from 0.33 to 0.94. In pair-wise comparison, the maximum  similarity was obtained between genotype with a similarity index of 0.32 to  0.50, whereas genotype showed least similarity with other genotypes.
Keywords: Cluster analysis; correlation; fruit yield; heritability; path analysis; variability